The MAL Blood Group System: Discovery, Characteristics, and Clinical Implications Mini Review - Almeida, Jocelin Harriate D; Ankitha Gururaj Bhat; Akshaya Kotian (Jurnal Vokasi Kesehatan, 2024)
The inherited AnWj-negative blood group phenotype is caused by homozygosity for a deletion in MAL, encoding Myelin and lymphocyte protein. Mal protein is expressed on red blood cell membranes of AnWj-positive, but not AnWj-negative, individuals.The 50-year-old enigma has been resolved with the discovery of a new blood group, MAL. Researchers from the University of Bristol, NHSBT's International Blood type Reference Laboratory (IBGRL), and NHS Blood and Transplant (Bristol) have determined the genetic foundation of the previously reported but enigmatic AnWj blood type antigen. The results make it possible to identify and treat rare patients who do not have this blood group. This mini review highlights on recent discovery of MAL blood group system after 50 years , to avoid transfusion reactions in the patients.